Teacher Exemplary Behavior in Character Learning: A Case Study on the Formation of Longed-for Teachers in Madrasah Ibtidaiyah - Mehamad Shaleh Gunung; Khozin; Rahmad Hakim (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2026)
This study aims to examine teacher exemplary behavior in character learning and its contribution to the formation of teachers who are longed for by students. The study employed a qualitative approach with a case study design at MI Muhammadiyah Tahuna. Data were collected through observation, in-depth interviews, and documentation involving teachers and students as the main participants. The data were analyzed through data condensation, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings show that teacher exemplary behavior was reflected in discipline, honesty, responsibility, polite communication, empathy, fairness, emotional control, and consistency between words and actions. These behaviors functioned as moral models that students observed, imitated, and internalized in daily school life. Teacher exemplary behavior also influenced students’ motivation and character by encouraging punctuality, confidence, respect, responsibility, and positive classroom participation. In addition, warm communication, active listening, and emotional support strengthened teacher–student relationships and created emotional closeness. This emotional bond contributed to the formation of the longed-for teacher, namely a teacher who is respected, remembered, and missed because their presence provides comfort, guidance, motivation, and moral inspiration. The study concludes that teacher exemplary behavior is a fundamental foundation of character learning and should be strengthened through reflective teaching practices, empathetic communication, and a supportive school culture.